Information System Design of Online-Based Technology News Forum - Ellyzabeth Sukmawati; Iwan Adhicandra; Nur Sucahyo; Astika Ayuningtyas; Nurwijayanti KN (International Journal of Artificial Intelligence Research, 2022)
In this study, researchers will create a news forum that processes data and information, especially in technology. As can be seen at this time, people still get information and express their opinions only through print media or what is commonly called newspapers or magazines, so the information may not be up to date quickly. Therefore, here the researcher will make observations and collect data to find out the main problems researchers will face when they want to make this news forum. There are several methods used to obtain the desired data, namely by conducting a literature study, namely the data collection method by collecting literature, journals, papers, and readings related to the research title, then creating a questionnaire that will be given to editors, journalists, as well as ordinary users in creating a news portal, in which there is a communication forum using existing methods such as Waterfall. The software for making this news portal and forum uses the programming languages Php, Mysql, Javascript, and CSS. Later following the results of observations, surveys and tests carried out, it is hoped that the information system that has been built can help be better than the applications previously used in processing data. In other words, the information system built will be able to process well-structured photo and news data. Ultimately, creating portals and forums helps people get information and express their opinions. This portal and forum design displays several menus, such as the latest news and profiles, and is supported by a communication forum.